The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1161/jaha.123.031322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Lipoprotein(a) on Long‐Term Survival Following Coronary Artery Bypass Grafting

Shuo Yuan,
Fangzhou Li,
Heng Zhang
et al.

Abstract: Background Lipoprotein(a) is a possible causal risk factor for atherosclerosis and related complications. The distribution and prognostic implication of lipoprotein(a) in patients undergoing coronary artery bypass grafting remain unknown. This study aimed to assess the impact of high lipoprotein(a) on the long‐term prognosis of patients undergoing coronary artery bypass grafting. Methods and Results Consecutive patients with stable corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Long-term prognosis in patients with coronary artery disease (CAD) after coronary artery bypass grafting (CABG) depends not only on preoperative factors (initial severity of coronary disease and myocardial condition, comorbidity, level of pathological biomarkers) [1][2][3], but also from further treatment and rehabilitation measures. The task of secondary prevention in this category of patients Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term prognosis in patients with coronary artery disease (CAD) after coronary artery bypass grafting (CABG) depends not only on preoperative factors (initial severity of coronary disease and myocardial condition, comorbidity, level of pathological biomarkers) [1][2][3], but also from further treatment and rehabilitation measures. The task of secondary prevention in this category of patients Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, most studies have focused on identifying baseline factors associated with long-term prognosis after CABG. For example, recent studies have shown the prognostic impact of biomarkers such as lipoprotein (a) [3] and LDL/HDL ratio [2] during 10-year follow-up of patients after CABG. The presence of a large number of risk factors and biomarkers that need to be adjusted and monitored when managing this category of patients creates certain inconvenience for practitioners and can lead to excessive expenditure of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term prognosis in patients with coronary artery disease (CAD) after coronary artery bypass grafting (CABG) depends not only on preoperative factors (initial severity of coronary disease and myocardial condition, comorbidity, level of pathological biomarkers) [1][2][3], but also from further treatment and rehabilitation measures. The task of secondary prevention in this category of patients is to level out those unfavorable risk factors that led to the CAD development, and, ultimately, to the need for myocardial revascularization [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, most studies have focused on identifying baseline factors associated with long-term prognosis after CABG. For example, recent studies have shown the prognostic impact of biomarkers such as lipoprotein (a) [3] and LDL/HDL ratio [2] during 10-year follow-up of patients after CABG. The presence of a large number of risk factors and biomarkers that need to be adjusted and monitored when managing this category of patients creates a certain inconvenience for practitioners and can lead to excessive expenditure of resources.…”
Section: Introductionmentioning
confidence: 99%